2018
DOI: 10.1364/boe.9.003821
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric macro- and micro-scale assessment of crystalline lens opacities in cataract patients using long-depth-range swept source optical coherence tomography

Abstract: We demonstrate an optimized optical platform for the three-dimensional (3-D) visualization of crystalline lens opacities in vivo in the eyes of patients with different types and grades of cataracts. We developed a prototype long-depth-range swept source optical coherence tomography (SS-OCT) instrument operating at the speed of 50 kA-scans/second and at the central wavelength of 1 μm to perform high-resolution imaging of the whole anterior segment of the eye. Volumetric data sets of cataractous eyes were acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 42 publications
2
23
0
1
Order By: Relevance
“…Some investigators have proposed the use of two-dimensional 50 53 or three-dimensional 54 OCT images to grade the scattering produced by the nucleus of the lens and have found a positive correlation with the subjective clinical lens opacification scale using a slit lamp. Recently, Grulkowski et al demonstrated that a custom-built 3-D OCT scanner enabled volumetric visualization of the detailed structure in the human crystalline lens in vivo and suggested that 3-D OCT is a useful tool for high-resolution evaluation and management of crystalline lens opacities in cataract patients 55 . Chen et al 52 and Panthier et al 56 demonstrated IOLMaster 700, a widely available 2-D OCT scanner on clinical setting, is a reliable and repeatable method for assessment of cataract compared to LOCS III scale, Scheimpflug imaging or double-pass aberrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have proposed the use of two-dimensional 50 53 or three-dimensional 54 OCT images to grade the scattering produced by the nucleus of the lens and have found a positive correlation with the subjective clinical lens opacification scale using a slit lamp. Recently, Grulkowski et al demonstrated that a custom-built 3-D OCT scanner enabled volumetric visualization of the detailed structure in the human crystalline lens in vivo and suggested that 3-D OCT is a useful tool for high-resolution evaluation and management of crystalline lens opacities in cataract patients 55 . Chen et al 52 and Panthier et al 56 demonstrated IOLMaster 700, a widely available 2-D OCT scanner on clinical setting, is a reliable and repeatable method for assessment of cataract compared to LOCS III scale, Scheimpflug imaging or double-pass aberrometry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fixation target, volunteer's movements are limited by the use of a dental impression. Figure 2 shows two OCT images of crystalline lenses affected by cataract [18,19]. Some regions remain transparent with the spatial distribution depending on the type of cataract.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its high-detection sensitivity, OCT technology allows detecting reflected signals of 5 × 10 −10 of the incident average laser power using only 20 μW [36]. The use of OCT in ophthalmology was first applied to visualize the human retina, emerging as a powerful complement of fundus photography in the interpretation and diagnosis of retinal diseases [37][38][39][40] and assessment of cataracts [41,42].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%